Analysis on the Legal Mechanisms for Consumer Protection in the Comparative Right, the Role and Importance of these Legal Mechanisms in Kosovo (European Journal of Marketing and Economics, 2022)
In this paper we would like to analyse and to treat the legal bases of: Legal analysis on the legal mechanisms for consumer protection in the comparative right, the role and importance of these legal mechanisms in developed countries and paying attention by special emphasis over the Republic of Kosovo. An important highlight will be over the comparative aspect of legal analysis in Kosovo, Macedonia and Albania. We also take into consideration the legal analysis of cases of violations and misleading commercial practices. Commercial practice is misleading when it contains false information and is therefore untrue. A commercial practice is misleading even when, in every possible way, including the overall appearance, misleads or is likely to mislead the average consumer, making or likely to make the consumer. The paper aims to provide a complete overview of the key issues related to the legal mechanisms for consumer protection in comparative law by treating them both theoretically and in the way that judicial practice, especially our judicial practice, has understand and apply procedural provisions regarding legal mechanisms for consumer protection in comparative law and issues arising in this regard. In this regard, the research questions include: 1. which are the main problems facing Kosovo's judicial practice in the context of the implementation of substantive and procedural provisions on cases and legal mechanisms for the protection of consumers in comparative law? 2.Is Kosovo facing poor implementation of the law, respectively non-implementation of material provisions and procedural provisions in Kosovo, for the protection of businesses and consumers? What are the causes that may affect the non-implementation of the legal framework, which is thought to be the best solution in this regard? The research questions that come out under the law are; in which cases should a relationship be referred to legal remedies for consumer protection in comparative foreign law? All these issues tend to give a comparative look at the international and national level. The expected results from this research consist in deepening theoretical and practical knowledge on legal mechanisms for consumer protection in comparative law, comparative analysis in Kosovo and beyond.
Keywords: Legal relationship, civil service, civil servants, recruitment, training, legal aspect, the Civil Service Commission, consumer role